Case report: Preliminary study on the diagnosis and treatment of respiratory distress in patients with giant nodular goiter complicated with severe COVID-19 - Wang, Fang; Yu, Xing; Ren, Zhangxia; Wang, Yong (Frontiers in Medicine, 2023)
Background To investigate the practicality of emergency surgical and conservative medical treatments in patients with giant nodular goiter complicated by severe coronavirus disease 2019 (COVID-19)-related respiratory distress, evaluate the prognosis based on the two interventions, and explore the diagnosis and treatment plan of COVID-19-related respiratory distress in patients with giant nodular goiter. Methods Four cases were retrospectively collected. Among them, two cases underwent emergency surgery, one case was treated with conservative treatment, whereas the fourth case underwent emergency surgery after failure of conservative therapy. Results Dyspnea was significantly improved postoperatively, and the endotracheal tube was successfully removed 10.5 h after the operation, but inflammatory markers were greatly enhanced as compared to the preoperative values, patients with different degrees of fever, cough, and other discomforts postoperatively. Case 1 showed complete remission of all symptoms after 3 weeks, while case 2 displayed fever, cough, drowsiness, and other symptoms after the discharge and was eventually readmitted. In case 3, the conservative COVID-19 treatment marginally improved the pulmonary infection, fever, and other symptoms, but cough and other discomforts were persistent, along with delirium in later stages. Moreover, case 4 reported extubation failure after undergoing treatment with the standard new coronary pneumonia regimen in the tracheal intubation state; however, the patient was successfully weaned and extubated 9 days after emergency surgery to relieve the obstruction. Conclusion Our preliminary exploration suggested that patients with giant nodular goiter and respiratory tract obstruction post-acute COVID-19 infection can undergo early surgery after surgical tolerance evaluation for a better prognosis.